Mechanisms For Promoting National Values Through Sports Events (Open Academia: Journal of Scholarly Research, 2026)
This article examines the mechanisms for promoting and popularizing national values through sports events in the context of contemporary social development. Sports events are analyzed not only as competitive platforms, but also as socio-cultural institutions that shape public consciousness, strengthen national identity, and transmit moral and cultural traditions. The study highlights the role of symbolic elements such as national symbols, traditional rituals, cultural programs, and media representations integrated into sports events. Particular attention is paid to the educational and ideological potential of sports festivals, national competitions, and international tournaments in strengthening patriotism and social cohesion. The article also discusses the influence of globalization and mass culture on the interpretation of national values within sports environments. As a result, the research proposes a conceptual approach to improving organizational, informational, and cultural strategies aimed at ensuring the sustainable dissemination of national values through sports events.